Synthesis of layered organicinorganic nanohybrid zincaluminium-2-(4-chlorophenoxy)-2-methyl propionic acid with controlled release properties - Sarijo S.H.; Ahmad A.; Muhsin S.M.N.; Jubri Z. (Springer New York LLC, 2023)
Fourier transform infrared spectroscopy; Nanostructured materials; Propionic acid; Saturated fatty acids; Sulfur compounds; Zinc; BET surface area; Controlled release; Controlled release properties; Layered double hydroxides; Layered Structures; Loading percentages; Nano-hybrid composites; Plant growth regulators; Aluminum compounds